Post-interview Thank-you Communications Influence Both Applicant and Residency Program Rank Lists in Emergency Medicine - Jewell, Corlin (West J Emerg Med, 2020)
INTRODUCTION: The National Residency Matching Program (NRMP) allows post-interview contact between residency applicants and residency programs. Thank-you communications represent one of the most common forms, but data on their value to applicants and program directors (PD) are limited. The objective of this study was to assess the effect of thank-you communications on applicant- and residency-program rank lists. METHODS: Two anonymous, voluntary surveys were sent after the 2018 NRMP Match, one to applicants who were offered an interview at a single academic site in the 2017–2018 Match cycle, and one to EM PDs nationwide. The surveys were designed in conjunction with a nationally-recognized survey center and piloted and revised based on feedback from residents and faculty. RESULTS: Of 196 residency applicants, 97 (49.5%) responded to the survey. Of these, 73/95 (76.8%) reported sending thank-you communications. Twenty-two of 73 (30%) stated that they sent thank-you communications to improve their spot on a program’s rank list; and 16 of 73 (21.9%) reported that they changed their rank list based upon the responses they received to their thank-you communications. Of 163 PDs, 99 (60.7%) responded to the survey. Of those PDs surveyed, 22.6% reported that an applicant could be moved up their program’s rank list and 10.8% reported that an applicant could move down a program’s rank list based on their thank-you communications (or lack thereof). CONCLUSION: The majority of applicants to EM are sending thank-you communications. A significant minority of applicants and PDs changed their rank list due to post-interview thank-you communications.